InP Wafer Dicing Protection Liquid, Preparation Method, Cleaning Liquid and Cleaning Method

By developing a cutting protection liquid for InP wafers, the problem of fragility and fine lines in the process of processing and cutting of InP wafers is solved, and the protection effect of high adhesion and good water resistance is achieved, which significantly improves the yield and production efficiency.

CN117070272BActive Publication Date: 2025-06-03ZHEJIANG AUFIRST MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310778540.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2025-06-03
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

InP wafers are prone to fragile and fine lines during processing, and are susceptible to scratches by particles and water flow during cutting, resulting in low yield, high cost and low production efficiency.

Method used

A cutting protective liquid for InP wafers is developed, containing side chain phenyl resin, composite emulsifier and leveling agent, which can form a protective layer with high adhesion and good water resistance, prevent fragmentation, fine lines and scratches, and is equipped with a special cleaning liquid to thoroughly clean the protective layer.

Benefits of technology

It significantly improves the cutting protection performance of InP wafers, reduces the occurrence of fragmentation and fine lines, improves the yield rate, reduces costs, enhances production efficiency, and avoids leakage problems in subsequent packaging processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117070272B_ABST
    Figure CN117070272B_ABST
Patent Text Reader

Abstract

The present invention provides a cutting protection liquid for InP wafers, its preparation method, usage method, and a cleaning liquid and cleaning method dedicated thereto. The protection liquid contains a side-chain phenyl resin and a composite emulsifier, and has excellent cutting protection performance. By using specific surfactants and corrosion inhibitors, the cleaning liquid can be dedicated to the cleaning of the cutting protection liquid, has a small residual film, and can inhibit electrode corrosion. The technical solutions such as the cutting protection liquid and the cleaning liquid can be applied to the semiconductor processing field, and have broad application prospects and promotion value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition used in semiconductor processing, a preparation method, uses, a special cleaning solution containing the same, a cleaning method, etc. More specifically, it relates to a protective liquid for ultra-thin wafer dicing, a preparation method thereof, uses thereof, a special cleaning solution containing the same, a cleaning use of the cleaning solution, a cleaning method using the cleaning solution, etc. in multiple specific aspects, belonging to the field of precision semiconductor processing technology and applications. Background Art

[0002] In recent years, the technological development of computers, communications, aerospace industries, and other consumer products has put forward higher miniaturization requirements for microelectronic packaging. The required wafers need to be thinned to less than 100 μm to make ultra-thin chips (usually the chip thickness is less than 100 μm).

[0003] Ultra-thin wafers have characteristics such as flexibility, fragility, and easy warping, and have high requirements for indicators such as total thickness variation (TTV), flatness (TIR), and warpage (Warp) of the wafers. For preventing breakage, usually, the wafer is temporarily bonded to a thicker carrier substrate with an intermediate medium first, and the carrier substrate provides structural support for it. After exposing the back surface of the wafer and completing the back thinning or other back processes, it is separated. This process is called temporary bonding - debonding. Before debonding and after temporary bonding is completed, the thickness is reduced by means of lapping on a lapping plate.

[0004] The back thinning process refers to: in the semiconductor chip manufacturing process, the chip is first fabricated on the front surface of the wafer. Due to subsequent processes such as back electrode and cleavage, and for reasons such as improving the heat dissipation performance of the chip, a part of the substrate on the back surface of the wafer is removed. This process is called back thinning. Generally, the back thinning process includes 4 steps: temporary bonding, grinding, debonding, and cleaning.

[0005] In compound semiconductor devices, indium phosphide (InP) is a compound semiconductor composed of group III element indium and group V element phosphorus. It is a brittle material itself, with a tensile stress much greater than the shear stress. Its mechanical properties tend to be brittle and it is easy to cleave (the fracture energy is only 0.63 J / m 2 ), and it is easy to break; in addition, its Knoop hardness (537) is smaller than that of common silicon Si (Knoop hardness is 1150). Therefore, InP has characteristics such as low hardness, high brittleness, and easy cleavage. After single crystal growth and cutting, InP semiconductor standard wafers (hereinafter sometimes also referred to as "InP wafers" or "InP semiconductor wafers, which have the same referential meaning") can be obtained. Optoelectronic chips such as detectors and lasers can be fabricated on the surface of InP semiconductor standard wafers, and thus are used in the fields of optical communication and optoelectronics.

[0006] As described above, due to the low hardness, high brittleness, and easy cleavage of InP materials, the fracture strength of InP semiconductor standard wafers becomes even smaller after the thickness is thinned, and it is more likely to be broken and scrapped due to fracture. Therefore, special attention should be paid to the protection of InP chips in semiconductor processing to prevent excessive mechanical stress from damaging the chips.

[0007] In addition, this type of InP chip belongs to a surface device, and its main components such as various optoelectronic components are fabricated in the epitaxial layer about 15 μm away from the surface on the front side of the wafer. The epitaxial layer is the core functional area for realizing "light - electricity" and "electricity - light" conversion, with a complex and fragile microstructure. At the same time, crystal defects inside the chip, such as lattice dislocations or point defects, will directly lead to the deterioration of chip performance or even failure and scrapping.

[0008] Therefore, for such a precise InP chip, the inherently damaging back - thinning process is very likely to damage the wafer, which poses a high - level process challenge to achieving excellent chip protection.

[0009] In addition, in the semiconductor packaging process, die saw is an important step, but the die - sawing process is also the main reason for the reduction in the qualification rate of various precision electronic components fabricated on the wafer. For a more detailed explanation of this reason, please refer to Figure 1 , which is a flowchart of the traditional wafer - cutting method.

[0010] As Figure 1 shown, first, a tape (such as the existing blue tape) is adhered to the back side of the wafer to be cut (i.e., the side without component formation) (step 10). Among them, since the back side of the ultra - thin wafer is adhered by the tape, no fragments will be generated during cutting. Then, the wafer adhered with the tape is cut (step 12). Among them, during the cutting of the ultra - thin wafer, it is usually necessary to spray - wash the ultra - thin wafer with water. Subsequently, the diced chips will continue with the die - mount process.

[0011] In Figure 1In the process of the conventional die cutting method shown, when the ultra-thin wafer is being cut, particles will be generated at the cutting position of the ultra-thin wafer, and the particles are easily lifted and fall onto the ultra-thin wafer. At the same time, during the transfer process of the cut ultra-thin wafer, many particles in the environment will fall on the surface of the ultra-thin wafer. Many high-end precision wafers (such as optoelectronic components made on the InP ultra-thin wafer) are highly sensitive to particles, so their qualified rate will be greatly reduced; at the same time, during the cutting process, water will be sprayed on the blade and the ultra-thin wafer to cool down. The high-speed rotating blade wheel will generate a water flow with a certain impact force and containing cutting debris. The water flow splashes onto the surface of the ultra-thin wafer and scratches will occur, resulting in a further decrease in the qualified rate.

[0012] In summary, for InP wafers, in their multiple semiconductor processing processes, they need to simultaneously meet the requirements of their own physical properties such as low hardness, high brittleness, easy cleavage, and the requirements of reducing damage during grain cutting. This puts strict requirements on its protection process. However, to date, there is no existing technology specifically for protecting InP wafer processing, especially for the protective liquid that prevents cracking, contamination, etc. during the cutting process. There has been no report, resulting in the current process using only conventional cleaning liquids and protective liquids, resulting in a lot of room for improvement in its yield rate, and significantly increasing the cost consumption in the process and reducing production efficiency.

[0013] Therefore, there is a need to improve the processing fluid to prevent InP wafers from cracking and fine lines during processing, as well as to prevent pollution and scratches during wafer cutting. This has very important practical significance and needs for industrial upgrading, improving product yield, and reducing losses. Summary of the invention

[0014] The present invention is developed and designed to prevent InP wafers from breaking and producing fine lines during grain cutting, to prevent particles from falling onto the wafer during cutting, and to further prevent the debris generated by cutting from scratching the precision structures on the surface of the ultra-thin wafer (such as various optoelectronic precision components thereon).

[0015] The present invention aims to provide a cutting protection liquid for InP wafers and related technical solutions (including its preparation method, cutting protection method using the same, uses, cleaning liquid dedicated to the same, preparation method and cleaning method, etc.). The protection liquid and / or cleaning liquid do not affect the normal use of the blue film adhered to the back of the wafer, can avoid curling and wrinkling of the blue film (if curling or wrinkling occurs, it will cause the InP wafer to be very easily unprotected, resulting in fine lines or even cracking), and has excellent film-forming performance and uniformity of dissolution performance. Further, the cleaning liquid does not contain metal ions, which can avoid leakage problems in subsequent packaging processes, and specific components therein can clean thoroughly and can inhibit electrode corrosion, etc. With these remarkable excellent effects, the processing qualification rate of precision semiconductor components can be significantly improved.

[0016] It should be noted that in the present invention, unless otherwise specified, the specific meaning of "including" related to composition limitations and descriptions includes both the open "including", "containing" and their similar meanings, and also the closed "consisting of..." and their similar meanings.

[0017] The present invention mainly relates to the following specific technical solutions.

[0018] [The first technical solution]

[0019] In the first technical solution, an object of the present invention is to provide a cutting protection liquid for InP wafers (hereinafter sometimes also referred to as "cutting protection liquid" or "protection liquid" or "wafer cutting protection liquid", and the three have the same referential meaning).

[0020] The wafer cutting protection liquid, in parts by mass, includes the following components:

[0021]

[0022] In the cutting protection liquid of the present invention, the side-chain phenyl resin is 10 - 40 parts by mass, and can be, for example, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts or 40 parts.

[0023] The side-chain phenyl resin is selected from styrene-based binary copolymers, styrene-based ternary copolymers, such as styrene-alkenyl sulfonic acid copolymer, styrene-alkenyl sulfonate copolymer, styrene-alkenyl sulfonic acid-acrylate copolymer, styrene-alkenyl sulfonic acid-acrylate copolymer, styrene-acrylic acid copolymer, styrene-acrylate copolymer, styrene-acrylic acid-acrylate copolymer, styrene-acrylate-acrylate copolymer; preferably one or more of styrene-alkenyl sulfonic acid copolymer, styrene-alkenyl sulfonic acid-acrylate copolymer, styrene-acrylic acid copolymer, styrene-acrylic acid-acrylate copolymer.

[0024] It should be noted that these resins are all well-known existing resins, and these resins of various specifications (such as different molecular weights such as number-average molecular weight) can be purchased through various commercial channels, and no detailed description will be given here.

[0025] Furthermore, the side-chain phenyl resin is more preferably a resin with an acidic group and a phenyl group on the side chain, such as a styrene-vinylsulfonic acid copolymer.

[0026] Among them, the vinylsulfonic acid in the styrene-vinylsulfonic acid copolymer is selected from vinylsulfonic acid, propenesulfonic acid, allylsulfonic acid, styrenesulfonic acid, methacrylic acid, allyloxyhydroxypropylsulfonic acid, and most preferably styrenesulfonic acid (i.e., well-known p-styrenesulfonic acid).

[0027] That is, the most preferred side-chain phenyl resin is a styrene-styrenesulfonic acid copolymer with an acidic group on the side chain.

[0028] The number-average molecular weight of the side-chain phenyl resin is preferably 1,000-50,000, and most preferably 3,000-10,000.

[0029] In the cutting protection liquid of the present invention, the mass parts of the composite emulsifier are 0.5-5 parts, for example, 0.5 part, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts.

[0030] Among them, the composite emulsifier is composed of an anionic emulsifier and a non-ionic emulsifier with a mass ratio of 1:1.5-5.

[0031] Among them, the anionic emulsifier is any one or a mixture of any multiple of sodium stearate, sodium dodecylsulfonate (i.e., n-dodecylsulfonate), sodium dodecylsulfate (i.e., n-dodecylsulfate), and sodium dodecylbenzenesulfonate (i.e., n-dodecylbenzenesulfonate).

[0032] Among them, the non-ionic emulsifier is any one or a mixture of any multiple of the OP series and the Tween series.

[0033] The OP series emulsifiers can be, for example, OP-10, OP-20, etc.; the Tween series can be, for example, Tween-20, Tween-40, Tween-60, etc.

[0034] Most preferably, the composite emulsifier is a mixture of sodium dodecylbenzenesulfonate and Tween-20 with a mass ratio of 1:3.

[0035] In the cutting protective liquid of the present invention, the leveling agent is 0.5 - 5 parts by mass, and for example, it can be 0.5 part, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts.

[0036] The leveling agent is selected from any one or a mixture of any multiple of waterborne acrylate leveling agents (such as acrylate modified copolymers, ionic polyacrylate copolymers, etc.), waterborne polyurethane leveling agents (such as nonionic waterborne polyurethanes, etc.), and waterborne silicone leveling agents (such as polyether modified siloxanes, etc.).

[0037] Furthermore, the leveling agent can be, for example, any one or a mixture of any multiple of BYK - 333, BYK - 348, Dow Corning Z - 6300, Keying KYC - 616, Mitsukoshi SY - 392, Chunmei Chemical KP - 140, Degussa TEGO4100.

[0038] In the cutting protective liquid of the present invention, the deionized water is 20 - 60 parts by mass, and for example, it can be 20 parts, 30 parts, 40 parts, 50 parts or 60 parts.

[0039] The inventor of the present invention found that in the cutting protective liquid of the present invention, by selecting specific and most preferred side - chain phenyl resins and compound emulsifiers, the best technical effects can be achieved (specifically, see the "Performance Characterization" section subsequently). For example, it has no influence on the appearance and adhesion of the blue film, and has many advantages such as strong adhesion and few residual particles, which can significantly improve the cutting protection performance of InP wafers, and thus can have good protection performance for various optoelectronic precision structures thereon.

[0040] In the cutting protective liquid of the present invention, the most preferred phenyl resin with acidic groups on the side chain has a small amount of strongly hydrophilic groups (i.e., sulfonic acid groups), a large number of aromatic groups (i.e., phenyl groups), and a main hydrophobic chain with an appropriate length. Through such a specific selection, it can be dissolved in the emulsion system formed by the interaction of compound emulsifier and deionized water as the main body in the form of micelles. In these micelles, the strongly hydrophilic groups face the outside of the micelles, and the hydrophobic chain segments face the inside of the micelles; when the deionized water dries and volatilizes, the emulsion system disappears. Due to the strong polarity exhibited by the hydrophobic chain segments, all face the air layer, endowing the coating with water resistance and forming a dense and highly adhesive hard protective coating on the wafer surface.

[0041] [Second technical solution]

[0042] The second technical solution, an object of the present invention is to provide a preparation method of the above - mentioned cutting protective liquid.

[0043] The preparation method includes the following steps:

[0044] A1: Weigh the required amount of deionized water;

[0045] A2: Weigh the required amounts of anionic emulsifier and non-ionic emulsifier;

[0046] A3: Mix the above components evenly and stir for 1 - 2 hours to obtain a mixed solution;

[0047] A4: Weigh the required amount of side-chain phenyl resin, add it to the mixed solution under stirring, and continue to stir for 2 - 4 hours until a transparent emulsion is obtained;

[0048] A5: Add the required amount of leveling agent to the transparent emulsion, and stir at room temperature for 0.5 - 1 hour until uniform to obtain the cutting protection liquid.

[0049] In the preparation method of the present invention, the stirring speed in steps A3 - A5 is not particularly limited, as long as it can mix each component evenly. Those skilled in the art can make appropriate selections and determinations according to the actual situation. Usually, for example, it can be 150 - 300 revolutions per minute, without particularly strict limitations.

[0050] [The third technical solution]

[0051] The third technical solution, an object of the present invention is to provide the use of the above cutting protection liquid in the cutting protection of InP wafers.

[0052] The cutting protection liquid has many advantages such as excellent blue film protection performance, film-forming performance, and uniformity of dissolution performance, can prevent particle contamination, has excellent protection adhesion, good protection for cutting channels, and the formed protective film is easy to clean and remove, etc., so it is particularly suitable for the cutting protection of high-precision and high-requirement precision wafers.

[0053] [The fourth technical solution]

[0054] The fourth technical solution, an object of the present invention is to provide a method for cutting protection of InP wafers using the above wafer cutting protection liquid, and the method includes the following steps:

[0055] B1: Drop 10 - 50 ml of the protection liquid onto the surface of the InP wafer, and use a spin coater to rotate at a speed of 500 - 1500 r / min for 30 - 60 s;

[0056] B2: Bake the wafer with the protection liquid spin-coated on its surface at 65 - 75 °C for 60 - 90 min to cure and form a protective film;

[0057] B3: Cut the wafer with the protective film on its surface, and enter the next process after cleaning.

[0058] Among them, in the step B1, the dropping amount of the protective liquid is 10-50 ml, for example, it can be 10 ml, 20 ml, 30 ml, 40 ml or 50 ml.

[0059] The rotation speed of the spin coater is 500-1500 r / min, for example, it can be 500 r / min, 1000 r / min or 1500 r / min; the rotation time is 30-60 s, for example, it can be 30 s, 40 s, 50 s or 60 s.

[0060] Among them, in the step B2, the wafer spin-coated with the protective liquid is baked at 65-75 °C for 60-90 min to cure into a film to form a protective layer. The baking temperature is 65-75 °C, for example, it can be 65 °C, 70 °C or 75 °C; the baking time is 60-90 min, for example, it can be 60 min, 70 min, 80 min or 90 min.

[0061] [The fifth technical solution]

[0062] The fifth technical solution, an object of the present invention is to provide a cleaning solution dedicated to the above-mentioned InP wafer cutting protective liquid, which can simply and quickly clean and remove the protective layer formed by the above-mentioned protective liquid, so as to continue with the subsequent processes.

[0063] In terms of parts by mass, the cleaning solution includes the following components:

[0064] Water-soluble surfactant 5-20

[0065] Corrosion inhibitor 1-5

[0066] Ultra-pure water 50-80

[0067] In the cleaning solution of the present invention, the mass fraction of the water-soluble surfactant is 5-20 parts, for example, it can be 5 parts, 10 parts, 15 parts or 20 parts.

[0068] The water-soluble surfactant is selected from any one or any mixture of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sodium stearate, lauric acid soap, alkyl sulfonate, alkyl sulfate, alkyl benzene sulfonate, Keying KYC-643, BYK-3410.

[0069] Among them, the water-soluble surfactant is preferably any one or any mixture of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sodium stearate, lauric acid soap, alkyl sulfonate, alkyl sulfate, alkyl benzene sulfonate, BYK-3410.

[0070] Furthermore, the water-soluble surfactant is most preferably any one or a mixture of any multiple of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, alkyl sulfonate (such as sodium dodecyl sulfonate), alkyl benzene sulfonate (such as sodium dodecyl benzene sulfonate), and BYK-3410.

[0071] The most preferred surfactant is sodium dodecyl benzene sulfonate.

[0072] In the cleaning solution of the present invention, the mass portion of the corrosion inhibitor is 1 - 5 parts, for example, it can be 1 part, 2 parts, 3 parts, 4 parts, or 5 parts.

[0073] Among them, the corrosion inhibitor is any one or a mixture of any multiple of L-cysteine, glutamic acid, aspartic acid, isoleucine, sodium silicate, sodium metasilicate, sodium fluorosilicate, trisodium phosphate, sodium dichromate, boric acid, tartaric acid, tannic acid, citric acid, glucose, and sodium alginate.

[0074] Furthermore, the corrosion inhibitor is preferably any one or a mixture of any multiple of L-cysteine, aspartic acid, sodium silicate, sodium metasilicate, sodium fluorosilicate, trisodium phosphate, boric acid, tartaric acid, tannic acid, and sodium alginate.

[0075] Most preferably, the corrosion inhibitor is one or a mixture of any multiple of L-cysteine, sodium silicate, trisodium phosphate, boric acid, tartaric acid, citric acid, tannic acid, or sodium alginate.

[0076] Even more preferably, the corrosion inhibitor is a mixture of L-cysteine and sodium alginate with a mass ratio of 1:1 - 3.

[0077] In the cleaning solution of the present invention, the mass portion of the ultrapure water is 50 - 80 parts, for example, it can be 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, or 80 parts.

[0078] The ultrapure water is deionized water with a resistance ≥ 18 MΩ.

[0079] The cleaning solution dedicated to the above-mentioned cutting protection fluid has many excellent technical effects. For example: the component with the largest proportion in it is water, which is the same as the component with the largest amount in the protection fluid, so that the cleaning conditions are mild and have no impact on the precision structures on the blue film and the chip; the selection and use of the corrosion inhibitor can significantly improve the effect of inhibiting the corrosion of aluminum electrodes, etc.

[0080] [Sixth Technical Solution]

[0081] Sixth technical solution, an object of the present invention is to provide a preparation method of the cleaning solution, and the specific preparation method is as follows: Weigh each component respectively, then add the water-soluble surfactant and the corrosion inhibitor into ultrapure water, and stir well. Then filter through a 0.2μm microporous filter membrane to obtain the cleaning solution.

[0082] [Seventh technical solution]

[0083] Seventh technical solution, an object of the present invention is to provide a cleaning method for cleaning the protective layer with the above cleaning solution (i.e., the "cleaning" treatment in step B3 of the above [Fourth technical solution]), and the cleaning method includes the following steps:

[0084] S1: Place the wafer coated with the protective layer in cleaning tank 1 filled with the cleaning solution, and soak it at a temperature of 50 - 60°C for 15 - 20 minutes;

[0085] S2: Transfer the wafer to cleaning tank 2 filled with the cleaning solution, and soak it at a temperature of 50 - 60°C for 15 - 20 minutes;

[0086] S3: Transfer the wafer to cleaning tank 3 filled with the cleaning solution, and soak it at a temperature of 50 - 60°C for 15 - 20 minutes;

[0087] S4: Transfer the wafer to the spraying area, and use ultrapure water to thoroughly clean the cleaning solution on the front and back of the wafer;

[0088] S5: Transfer the wafer to the air drying area, and dry the back of the wafer with hot nitrogen;

[0089] S6: Transfer the wafer to the cleaning machine, rotate it at a speed of 1000 - 1500 r / min for 120 - 360 s, and spray ultrapure water onto the wafer surface at a flow rate of 400 - 600 mL / min during this period;

[0090] S7: Stop spraying ultrapure water, rotate the wafer at a speed of 1500 - 2000 r / min for 120 - 360 s to spin-dry, and complete the cleaning treatment of the protective layer.

[0091] Among them, in the above steps S1 - S7, although the wafers to be cleaned have been cut in the [Fourth technical solution], this cutting is to first divide the whole wafer into individual grains, but the scribe line gaps formed after cutting are extremely narrow and difficult to distinguish with the naked eye. And at this time, all the grains are still closely arranged and adhered to the blue film on the back, and the overall appearance is no different from that of a complete wafer, still in the form of a whole wafer. Only after the film expansion process is carried out after cleaning, a relatively large gap will be formed between the grains, and then each grain core can be taken out one by one.

[0092] Among them, the ultrapure water involved above is deionized water with a resistance ≥ 18 MΩ.

[0093] Among them, in the steps S1 - S3, by adopting a multi - tank cleaning process, good technical effects can be achieved: 1. Multiple sub - tank treatments can avoid the problems of excessive protective coating shedding and re - adhesion secondary pollution accumulated in a single tank. 2. It can avoid the defect of a serious decline in cleaning efficiency caused by excessive protective coating shedding accumulated in a single tank.

[0094] In summary, the present invention provides a cutting protection liquid for InP wafers, a preparation method, uses, a wafer cutting protection method using this protection liquid, a cleaning liquid dedicated to this protection liquid, a preparation method of this cleaning liquid, and a protective layer cleaning method using this cleaning liquid. All the above - mentioned technical solutions have many advantages. For example:

[0095] 1. When the protection liquid cures on the surface of the InP wafer, due to the hydrophobicity of phenyl groups in the resin and the polarity difference of hydrophilic groups in the molecular structure, a hard, transparent, smooth protective layer with high adhesion that is insoluble in cold water but soluble in hot water can be formed.

[0096] 2. As described above, both the cleaning liquid and the protection liquid contain a large amount of water, and the number of their respective formulated components is small. The curing and cleaning conditions are mild and will not have any impact on the precision structures on the blue film and the chip. It is especially suitable for the cutting protection of InP wafers with a blue film adhered to the back.

[0097] 3. Due to the selection and use of a unique corrosion inhibitor (a complex of L - cysteine and sodium alginate) in the cleaning liquid, the corrosion of aluminum electrodes can be significantly inhibited.

[0098] 4. The components of the protection liquid and the cleaning liquid are all of low - toxicity or non - harmful components, are easy to recycle, treat, and discharge, have excellent environmental friendliness, and can achieve green production.

[0099] 5. In this method, the cleaning process combines multi - tank immersion and single - wafer rotary spray cleaning, which can improve the cleaning efficiency, greatly save the amount of cleaning liquid used, reduce cross - contamination, improve the cleaning yield, and reduce the sewage treatment cost.

[0100] 6. The protective layer formed by the protection liquid has technical effects such as protecting the blue film, long water - resistant time, high adhesion, and few residual particles. Furthermore, it can significantly improve the yield of subsequent semiconductor components, and improve the production effect and yield of the entire production line. BRIEF DESCRIPTION OF THE DRAWINGS

[0101] Attached Figure 1 is a flowchart of a traditional wafer cutting method with a glue film adhered to the back.

[0102] AttachedFigure 2 It is a photograph of the appearance of the protective liquid Y1.

[0103] Appendix Figure 3 (a) - 3(d) are photographs of InP wafers with adhered blue films immersed in the protective liquids Y1, Y13, Y7, and Y10 for 24 hours respectively.

[0104] Appendix Figure 4 (a) - 4(b) are 50 - fold magnified views of the surfaces of partial Dummy wafers (bare wafers) after spin - drying the cuts using the cutting protective liquids Y1 and Y7 respectively.

[0105] Appendix Figure 5 (a) is a microscope photograph of the optoelectronic component area on the InP wafer after cutting and coating with the protective liquid Y1, magnified 500 times.

[0106] Appendix Figure 5 (b) is a microscope photograph of the optoelectronic component area on the InP wafer after cutting without coating with the protective liquid, magnified 500 times.

[0107] Appendix Figure 6 (a) is a method photograph of the aluminum electrode immersed in the cleaning liquid Q1 for 1 hour under a 200 - fold microscope in dark - field.

[0108] Appendix Figure 6 (b) is a method photograph of the aluminum electrode immersed in the cleaning liquid DQ1 for 1 hour under a 200 - fold microscope in dark - field.

[0109] Appendix Figure 6 (c) is a method photograph of the aluminum electrode immersed in the cleaning liquid DQ4 for 1 hour under a 200 - fold microscope in dark - field. Detailed implementation manners

[0110] The present invention will be described in detail below through specific examples. However, the uses and purposes of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor will the protection scope of the present invention be limited thereto.

[0111] Among them, unless otherwise specified, any ultrapure water used below is deionized water with a resistance ≥ 18 MΩ.

[0112] Among them, for the side - chain phenyl resin used below, since it is a polymer, its molecular weight cannot be an accurate specific value, but is a range value of an interval. For example, when the molecular weight is 50,000, it does not mean that its accurate molecular weight is 50,000, but a suitable fluctuation range (for example, the molecular weight can be measured by a variety of well - known technical means). However, in commercially available products, it is marked as 50,000. Therefore, there is no need to worry about its actual precise molecular weight, but it should be defined according to conventional understanding and based on the markings of commercially available products.

[0113] Example 1: Preparation of InP Wafer Dicing Protective Liquid

[0114] A1: Weigh 40 parts by mass of deionized water;

[0115] A2: Weigh 2.8 parts by mass of a composite emulsifier, which consists of 0.7 part by mass of sodium dodecylbenzenesulfonate and 2.1 parts by mass of Tween-20;

[0116] A3: Mix the above components A1 and A2 evenly and stir for 1.5 hours to obtain a mixed solution;

[0117] A4: Weigh 25 parts by mass of styrene-styrenesulfonic acid copolymer with a number-average molecular weight of 6000, and then add it to the mixed solution obtained in step A3 with stirring, and continue stirring for 3 hours until a transparent emulsion is obtained;

[0118] A5: Add 2.5 parts by mass of leveling agent BYK-333 to the transparent emulsion, and stir at room temperature for 45 minutes until uniform, then the InP dicing protective liquid is obtained. Name it Y1, which is a slightly blue transparent liquid (see attachment Figure 2 ).

[0119] Among them, the stirring speed in steps A3 - A5 is 200 revolutions per minute.

[0120] Example 2: Preparation of InP Wafer Dicing Protective Liquid

[0121] A1: Weigh 20 parts by mass of deionized water;

[0122] A2: Weigh 0.6 parts by mass of a composite emulsifier, which consists of 0.15 part by mass of sodium dodecylbenzenesulfonate and 0.45 parts by mass of Tween-20;

[0123] A3: Mix the above components A1 and A2 evenly and stir for 1 hour to obtain a mixed solution;

[0124] A4: Weigh 40 parts by mass of styrene-styrenesulfonic acid copolymer with a number-average molecular weight of 6000, and then add it to the mixed solution obtained in step A3 with stirring, and continue stirring for 4 hours until a transparent emulsion is obtained;

[0125] A5: Add 0.5 parts by mass of leveling agent Keying KYC-616 to the transparent emulsion, and stir at room temperature for 1 hour until uniform, then the InP dicing protective liquid is obtained. Name it Y2, which is also a slightly blue transparent liquid (exactly the same as the attachment Figure 2 , so it is not listed again).

[0126] Among them, the stirring speed in steps A3 - A5 is 200 revolutions per minute.

[0127] Example 3: Preparation of InP Wafer Dicing Protectant

[0128] A1: Weigh 60 parts by mass of deionized water;

[0129] A2: Weigh 5 parts by mass of a composite emulsifier, which consists of 1.25 parts by mass of sodium dodecylbenzenesulfonate and 3.75 parts by mass of Tween-20;

[0130] A3: Mix the above components A1 and A2 evenly and stir for 2 hours to obtain a mixed solution;

[0131] A4: Weigh 10 parts by mass of styrene-styrenesulfonic acid copolymer with a number-average molecular weight of 6000, and then add it to the mixed solution obtained in step A3 under stirring, and continuously stir for 2 hours until a transparent emulsion is obtained;

[0132] A5: Add 5 parts by mass of leveling agent Degussa TEGO 4100 to the transparent emulsion, and stir at room temperature for 30 minutes until uniform, then the InP dicing protectant is obtained, which is named Y3. It is also a slightly blue transparent liquid (exactly the same as the appendix Figure 2 , so it will not be listed again).

[0133] Among them, the stirring speed in steps A3 - A5 is 200 revolutions per minute.

[0134] Examples 4 - 6: Preparation of InP Wafer Dicing Protectant

[0135] Except that the styrene-styrenesulfonic acid copolymer is replaced by styrene-vinylsulfonic acid copolymer, styrene-allylsulfonic acid copolymer and styrene-methacrylic acid copolymer respectively, and other operations / parameters remain unchanged, thus repeating Examples 1 - 3 in sequence to obtain Examples 4 - 6 correspondingly, and the obtained protectants are named Y4, Y5 and Y6 in sequence.

[0136] Examples 7 - 12: Preparation of InP Wafer Dicing Protectant

[0137] Examples 7 - 9: Except that the composite emulsifier is replaced by the single-component sodium dodecylbenzenesulfonate with the same total mass fraction respectively, and other operations / parameters remain unchanged, thus repeating Examples 1 - 3 in sequence to obtain Examples 7 - 9 correspondingly, and the obtained protectants are named Y7, Y8 and Y9 in sequence.

[0138] Examples 10 - 12: Except that the composite emulsifier is replaced by the single-component Tween-20 with the same total mass fraction respectively, and other operations / parameters remain unchanged, thus repeating Examples 1 - 3 in sequence to obtain Examples 10 - 12 correspondingly, and the obtained protectants are named Y10, Y11 and Y12 in sequence.

[0139] Examples 13 - 18: Preparation of InP Wafer Dicing Protection Liquid

[0140] Examples 13 - 15: Except that sodium dodecylbenzenesulfonate in the compound emulsifier was replaced with sodium stearate, sodium dodecyl sulfonate, and sodium dodecyl sulfate of the same mass fraction respectively, other operations / parameters remained unchanged. Thus, Examples 1 - 3 were sequentially repeated to obtain Examples 13 - 15 accordingly. The obtained protection liquids were named Y13, Y14, and Y15 in sequence.

[0141] Examples 16 - 18: Except that Tween - 20 in the compound emulsifier was replaced with Tween - 60, OP - 10, and OP - 20 of the same mass fraction respectively, other operations / parameters remained unchanged. Thus, Examples 1 - 3 were sequentially repeated to obtain Examples 16 - 18 accordingly. The obtained protection liquids were named Y16, Y17, and Y18 in sequence.

[0142] Blue film resistance test

[0143] 1. Immerse the InP wafer with a blue film adhesively fixed on the back surface in the dicing protection liquid Y1 for 24 hours. The result is as shown in Figure 3 (a): The appearance of the blue film shows no change, and it still adheres firmly to the wafer, that is, its adhesiveness shows no change.

[0144] After immersing it in the protection liquids Y2 - Y6 for 24 hours, the appearance and adhesiveness are exactly the same as those in Figure 3 (a), so they will not be listed one by one.

[0145] 2. Immerse the InP wafer with a blue film adhesively fixed on the back surface in the dicing protection liquid Y13 for 24 hours. The result is as shown in Figure 3 (b) (taken after tearing the blue film off the wafer): The four corners are slightly upturned, proving that its adhesiveness has decreased.

[0146] After immersing it in the protection liquids Y14 - Y18 for 24 hours, the appearance and adhesiveness are exactly the same as those in Figure 3 (b), so they will not be listed one by one.

[0147] 3. Immerse the InP wafer with a blue film adhesively fixed on the back surface in the dicing protection liquid Y7 for 24 hours. The result is as shown in Figure 3 (c) (at this time, the blue film is almost completely single - layer curled and can be detached from the wafer without any external force. This is taken after being taken out of the solution easily): It has almost completely detached from the wafer and has lost its adhesiveness.

[0148] After immersing it in the protection liquids Y8 - Y9 for 24 hours, the appearance and adhesiveness are exactly the same as those in Figure 3 (c), so they will not be listed one by one.

[0149] 4. Immerse the InP wafer with a blue film adhered to the back surface in the cutting protective liquid Y10 for 24 hours. The result is as shown in the appendix Figure 3 (d): The blue film completely falls off and curls into a cylindrical shape.

[0150] When it is immersed in the protective liquids Y11 - Y12 for 24 hours, the appearance and adhesion are exactly the same as those in the appendix Figure 3 (d), so they will not be listed one by one.

[0151] Thus, it can be seen that in the said cutting protective liquid, the emulsifier is preferably a composite emulsifier, and the most preferred composite emulsifier is the complex of sodium dodecylbenzenesulfonate and Tween - 20. When the type of the composite emulsifier changes to an anionic or non - ionic emulsifier or a single component is used, it may cause the adhesion of the blue film to decrease or even completely fall off, and it cannot be used in the semiconductor manufacturing process. This is because when the type of the anionic or non - ionic emulsifier changes, the protective liquid may easily penetrate from the edge to the inside between the blue film adhesive layer and the back surface of the wafer due to the change of the emulsifying ability and / or the penetrating ability, thereby reducing the bonding force of the blue film and causing the four corners to warp or even the whole to fall off.

[0152] Adhesion performance test of the protective layer after the protective liquid solidifies

[0153] The adhesion performance test of the protective layer is carried out according to the following method. Taking Y1 as an example, use Y1 to carry out cutting protection on the InP wafer as follows:

[0154] B1: Drop 30 ml of the protective liquid Y1 onto the surface of the InP wafer, and use a spin coater to rotate at a speed of 1000 r / min for 45 s;

[0155] B2: Bake the InP wafer with the protective liquid Y1 spin - coated on the surface obtained in B1 at 70 °C for 75 min to cure into a film to form a protective layer;

[0156] B3: Cut the wafer with the protective layer on the surface obtained in B2. The cutting operation is a very well - known cutting method (such as high - speed wheel cutting with water jet cooling, etc.), and after cutting, spin - dry the wafer.

[0157] After spin - drying, observe the adhesion of the protective layer. The specific results are as follows:

[0158] 1. Figure 4 (a) is a 50 - fold magnified view of the surface of a partial Dummy wafer after cutting and spin - drying using the cutting protective liquid Y1. It can be seen that the protective layer does not fall off at all, achieving complete protection of the wafer surface and preventing it from being contaminated by dirt, particles and other impurities.

[0159] When using the protective liquids Y2 - Y3, the magnified views of the wafer surface are the same as those ofFigure 4 (a) is exactly the same and achieves complete and thorough protection, so it will not be listed one by one.

[0160] 2. Figure 4 (b) is a 50-fold magnified view of the surface of a partial Dummy wafer after spin-drying the cut with the cutting protection liquid Y7. It can be seen that the protective layer has fallen off very significantly, and it is impossible to achieve complete and thorough protection of the wafer surface, thus it is impossible to avoid being contaminated by dirt, particles and other impurities.

[0161] When using the protection liquids Y4 - Y6, Y8 - Y18, the overall situation of the protective layer falling off is generally similar to that of Figure 4 (b), and there is also a certain area of peeling off. The specific data can be seen in Table 1 below.

[0162] In order to measure and compare more quantitatively, the percentage of the peeling area of the protective layer (i.e., the percentage of the peeling area to the area of the entire original protective layer) when using the protection liquids Y1 - Y12 is measured and calculated, and the results are shown in Table 1 below.

[0163] Table 1

[0164]

[0165] Among them, the peeling areas of Y1 - Y3 are all 0, while other protection liquids have a strict corresponding relationship with the percentage of the peeling area ratio. For example, taking "Y4 / Y5 / Y6" and "2.1 / 2.5 / 2.6" as an example, it means that the percentage of the peeling area of Y4 is 2.1%, the percentage of the peeling area of Y5 is 2.5%, and the percentage of the peeling area of Y6 is 2.6%. The same applies to Y7 - Y12 and the following same markings, and they will not be elaborated one by one here.

[0166] Thus, it can be seen that among the said cutting protection liquids, the side-chain phenyl resin is most preferably styrene - styrene sulfonic acid copolymer and the composite emulsifier is most preferably the composite of sodium dodecyl benzene sulfonate and Tween - 20. When changing the type of the side-chain phenyl resin or replacing the composite emulsifier with a single component or even changing the type of the non-ionic emulsifier or the anionic emulsifier, the adhesion force will be reduced. Especially when using a single-component emulsifier, the reduction is the most obvious.

[0167] The inventor believes that this should be because the structure of the styrene-styrene sulfonic acid copolymer is simple and regular. Its main chain is a C-C long chain after the opening of the ethylene double bond, and the side chains are single benzene ring groups and random styrene sulfonic acid groups. Due to the strong polarity of the benzene ring and the regularity of the structure, the styrene-styrene sulfonic acid copolymer shows a highly polar and tightly arranged structure during curing. The side facing the air is a single benzene ring group arranged, and the side facing the substrate is a styrene sulfonic acid group. The benzene ring group endows the coating with water resistance, ensuring that the coating will not fall off due to dissolution in water during the cutting process, while the styrene sulfonic acid group endows the coating with high adhesion, ensuring that the coating will not fall off due to radial impact force during the cutting process. The styrene-styrene sulfonic acid copolymer produces an optimal balance and synergy of water resistance and adhesion, thus having the best water resistance and adhesion. When changing the type of the side chain phenyl resin, many properties such as the polarity, regularity, and compactness of the copolymer will be changed, thus affecting properties such as adhesion.

[0168] For the emulsifier, the anionic emulsifier and non-ionic emulsifier in the composite emulsifier can produce a synergistic effect: the anionic emulsifier makes the macromolecular chain of the styrene-styrene sulfonic acid copolymer form micelles, and the non-ionic emulsifier makes the micelles dissolve uniformly in the water phase. However, not all combinations of anionic emulsifiers and non-ionic emulsifiers can produce the best synergistic effect. It is found that only sodium dodecylbenzenesulfonate and Tween-20 can produce the best effect. If their compatibility with the copolymer is poor, phase separation will occur between the emulsifier and the resin to a certain extent during the curing of the cutting protection liquid, thus affecting the water resistance and adhesion of the resin and resulting in easy shedding.

[0169] Particle protection performance of the protective liquid

[0170] 1. Figure 5 (a) is a microscope photograph of the optoelectronic component area on the InP wafer after cutting with the coating protection liquid Y1 magnified 500 times. It can be clearly seen that there are no foreign particles in this area (no white foreign bright areas), proving that it has very excellent cutting protection performance and can greatly improve the cutting yield of the chip.

[0171] The cutting protection results of using Y2 - Y3 according to the above method are exactly the same as Figure 5 (a), and will not be listed one by one here.

[0172] 2. When not using Y1 - Y3 for protection, that is, directly cutting the InP wafer, and then magnifying the optoelectronic component area 500 times, the microscope photograph obtained is shown in Figure 5 (b).

[0173] From Figure 5It can be clearly seen from (b) that there is a large area of irregular bright granular regions on it (foreign particles with a size greater than 2.0 microns). For such optoelectronic chips, even if there is only one foreign particle with a size greater than 2.0 microns, the chip will be a defective product, and these particles cannot be effectively removed by the current cleaning methods in the existing technology. This is because the cleaning liquids used in the current cleaning methods are mainly neutral, water-based strong alkaline or all-solvent cleaning liquids. However, when there are precision optoelectronic structures on the wafer, the precision structure cannot withstand the corrosion of strong alkaline and most solvents.

[0174] Therefore, the current cleaning methods are not suitable for the industrial and pipeline cleaning of wafers with precision optoelectronic structures, and thus cannot improve and meet the cleanliness requirements of their subsequent processes. Moreover, the product yield is too low to achieve large-scale and industrial production.

[0175] Water resistance test of the protective liquid

[0176] The water resistance tests were all carried out according to the following method: using a protective liquid to protect the InP wafer during cutting, specifically as follows:

[0177] B1: Drop 30 ml of the protective liquid onto the wafer surface and spin it at a speed of 1000 r / min for 45 s using a spin coater.

[0178] B2: Bake the wafer with the protective liquid spin-coated on its surface obtained in B1 at 70 °C for 75 min to cure into a film and form a protective layer.

[0179] After forming the protective layer, soak the wafer in deionized water for a certain period of time, then take out the wafer and spin it dry at a speed of 1000 r / min, and observe whether the protective layer peels off (as long as there is local peeling, it is considered to have peeled off), so as to determine the longest time without peeling. The specific results are shown in Table 2 below:

[0180] Table 2

[0181]

[0182] It can be seen from this that the protective liquid of the present invention has excellent water resistance, and the time can be up to about 70 minutes without peeling. However, when changing the type of resin polymer, the peeling time may be reduced (see Y4 - Y6). When using a single emulsifier or changing the component types in the composite emulsifier, the water resistance can be significantly reduced, especially when using a single emulsifier, the reduction is more obvious.

[0183] In all the following preparation examples, ultrapure water is deionized water with a resistance ≥ 18 MΩ.

[0184] Preparation Example 1: Preparation of the cleaning liquid

[0185] By mass, 12.5 parts of the water-soluble surfactant sodium dodecylbenzenesulfonate and 3 parts of a corrosion inhibitor (a mixture of 1 part of L-cysteine and 2 parts of sodium alginate) were added to 65 parts of ultrapure water, stirred well, and then filtered through a 0.2-μm microporous membrane to obtain a cleaning solution, which was named Q1.

[0186] Preparation Example 2: Preparation of a cleaning solution

[0187] By mass, 5 parts of the water-soluble surfactant sodium dodecylbenzenesulfonate and 5 parts of a corrosion inhibitor (a mixture of 2.5 parts of L-cysteine and 2.5 parts of sodium alginate) were added to 80 parts of ultrapure water, stirred well, and then filtered through a 0.2-μm microporous membrane to obtain a cleaning solution, which was named Q2.

[0188] Preparation Example 3: Preparation of a cleaning solution

[0189] By mass, 20 parts of the water-soluble surfactant sodium dodecylbenzenesulfonate and 1 part of a corrosion inhibitor (a mixture of 0.25 part of L-cysteine and 0.75 part of sodium alginate) were added to 50 parts of ultrapure water, stirred well, and then filtered through a 0.2-μm microporous membrane to obtain a cleaning solution, which was named Q3.

[0190] Comparative Preparation Examples 1-3: Preparation of a cleaning solution

[0191] Except that the sodium dodecylbenzenesulfonate in Preparation Examples 1-3 was replaced with sodium dodecylsulfonate in the same mass parts respectively, other operations / parameters remained unchanged. Thus, Preparation Examples 1-3 were sequentially repeated to obtain Comparative Preparation Examples 1-3 accordingly, and the obtained cleaning solutions were named DQ1, DQ2, and DQ3 in sequence.

[0192] Comparative Preparation Examples 4-9: Preparation of a cleaning solution

[0193] Comparative Preparation Examples 4-6: Except that the compound corrosion inhibitor was replaced with the single-component L-cysteine in the same total mass parts respectively, other operations / parameters remained unchanged. Thus, Preparation Examples 1-3 were sequentially repeated to obtain Comparative Preparation Examples 4-6 accordingly, and the obtained protective solutions were named DQ4, DQ5, and DQ6 in sequence.

[0194] Comparative Preparation Examples 7-9: Except that the compound corrosion inhibitor was replaced with the single-component sodium alginate in the same total mass parts respectively, other operations / parameters remained unchanged. Thus, Preparation Examples 1-3 were sequentially repeated to obtain Comparative Preparation Examples 7-9 accordingly, and the obtained protective solutions were named DQ7, DQ8, and DQ9 in sequence.

[0195] Electrode corrosion protection performance of the cleaning liquid

[0196] 1. Immerse the aluminum electrode in cleaning solution Q1 for 1 hour. Then, under the dark field of a 200 - fold microscope, it is found that the electrode does not show obvious brightness, which proves that the aluminum electrode has no obvious corrosion. See Appendix Figure 6 (a).

[0197] Similarly, immerse the aluminum electrode in cleaning solutions Q2 - Q3 respectively. Under the dark field of a 200 - fold microscope, it is also found that the electrode does not show obvious brightness, which also proves that the aluminum electrode has no obvious corrosion. Its magnified photos are exactly the same as Appendix Figure 6 (a), and will not be listed one by one here.

[0198] 2. When the aluminum electrode is immersed in cleaning solution DQ1 for 1 hour and then under the dark field of a 200 - fold microscope, it is found that the brightness of the electrode is stronger than that of Y1 - Y3, which proves that the aluminum electrode has a certain degree of corrosion. See Appendix Figure 6 (b).

[0199] Similarly, immerse the aluminum electrode in cleaning solutions DQ2 - DQ3 respectively. Under the dark field of a 200 - fold microscope, it is found that the brightness of the electrode is highly similar to Appendix Figure 6 (b), and will not be listed one by one here.

[0200] 3. Immerse the aluminum electrode in cleaning solution DQ4 for 1 hour. Then, under the dark field of a 200 - fold microscope, it is found that the electrode shows obvious brightness, which proves that the aluminum electrode has obvious corrosion. See Appendix Figure 6 (c), and its degree of corrosion is stronger than that of Appendix Figure 6 (b).

[0201] Similarly, immerse the aluminum electrode in cleaning solutions DQ5 - DQ9 respectively. Under the dark field of a 200 - fold microscope, it is also found that the electrode shows obvious brightness, and its electrode brightness is highly similar to Appendix Figure 6 (c), which proves that the aluminum electrode has obvious corrosion and will not be listed one by one here.

[0202] In summary, for the surfactant among them, sodium dodecylbenzenesulfonate is most preferred. For the corrosion inhibitor, a mixture of L - cysteine and sodium alginate is most preferred. When using a single - component corrosion inhibitor, it will cause the degree of electrode corrosion to become significantly stronger.

[0203] Cleaning performance test of the cleaning liquid

[0204] The cleaning operations in this "Cleaning Performance Test of Cleaning Solution" are all carried out according to the following method. Taking Y1 as an example, it is as follows:

[0205] B1: Drop 30 ml of protective liquid onto the surface of the InP wafer and rotate it at a speed of 1000 r / min for 45 s using a spin coater;

[0206] B2: Bake the wafer with the protective liquid spin-coated on its surface at 70 °C for 75 min to cure into a film and form a protective layer;

[0207] B3: Cut the wafer with the protective layer on its surface. The cutting operation is a very well-known cutting method (such as high-speed cutter wheel cutting with water jet cooling, etc.).

[0208] Among them, the above steps B1 - B2 are all carried out in a static Class 100 clean room to prevent impurities such as dust particles from falling on the wafer surface.

[0209] After the cutting in the above step B3 is completed, the following cleaning steps are carried out:

[0210] S1: Place the wafer with the protective layer coated in cleaning tank 1 filled with the cleaning liquid and soak it at a temperature of 55 °C for 17 min;

[0211] S2: Transfer the wafer to cleaning tank 2 filled with the cleaning liquid and soak it at a temperature of 55 °C for 17 min;

[0212] S3: Transfer the wafer to cleaning tank 3 filled with the cleaning liquid and soak it at a temperature of 55 °C for 17 min;

[0213] S4: Transfer the wafer to the spraying area and use ultrapure water to thoroughly clean the cleaning liquid on the front and back of the wafer;

[0214] S5: Transfer the wafer to the air drying area and blow dry the back of the wafer with hot nitrogen;

[0215] S6: Transfer the wafer to the cleaning machine and rotate it at a speed of 1200 r / min for 240 s. During this period, spray ultrapure water onto the wafer surface at a flow rate of 500 mL / min;

[0216] S7: Stop spraying ultrapure water, rotate the wafer at a speed of 1700 r / min for 240 s to spin dry and complete the cleaning process of the protective layer.

[0217] After the above cleaning process is completed, magnify the wafer 1000 times under a scanning electron microscope to observe the size of the residual film (this is a very well-known and common measurement and detection method, and will not be described in detail here). The specific results are shown in Table 3 below, where the listed data are the sizes of the largest residual films:

[0218] Table 3

[0219]

[0220] Thus, it can be seen that the cleaning solution of the present invention has excellent cleaning performance, and the maximum size of the remaining film is less than 0.5 μm, fully meeting the cleaning requirements of the optoelectronic region of InP wafers. When the type of surfactant is changed, even if the sodium dodecylbenzenesulfonate of Q1-Q3 is replaced with a similar sodium dodecylsulfonate, the residue is close to 2 μm (barely meeting the cleanliness requirements).

[0221] This is because sodium dodecylbenzenesulfonate has the best dissolving effect on the protective film formed by the protective liquid, and can quickly emulsify and decompose the protective film under heating conditions, transforming it from an aggregated state into a macromolecular chain of styrene-styrenesulfonic acid and dissolving it in the cleaning solution, thereby achieving complete cleaning. It can also be seen that when using a single-component corrosion inhibitor, the remaining film may also become larger. The reason may be that both L-cysteine and sodium alginate are molecular compounds prone to ionization. After ionization, they can adsorb on the macromolecular chain of styrene-styrenesulfonic acid, and the two can jointly increase and enhance the water solubility of the macromolecular chain, thereby significantly promoting the dissolution of the protective film. When using a single component, the synergistic effect of mutual promotion between the two disappears, resulting in a larger residue instead.

[0222] As described above, the present invention provides a cutting protective liquid for InP wafers and its related technical solutions (including its preparation method, cutting protection method using it, uses, cleaning liquid dedicated to it, preparation method and cleaning method, etc.). The protective liquid and / or cleaning liquid do not affect the normal use of the blue film attached to the back of the wafer, can avoid curling and wrinkling of the blue film (if curling or wrinkling occurs, it will cause the InP wafer to be very easily unprotected, resulting in fine lines or even cracking), and have excellent film-forming performance and uniformity of dissolving performance. Further, the cleaning liquid does not contain metal ions, which can avoid leakage problems in subsequent packaging processes, and specific components therein can clean thoroughly and inhibit electrode corrosion, etc. With these remarkable excellent effects, the processing qualification rate of precision semiconductor components can be significantly improved.

[0223] It should be understood that the uses of these embodiments are only for illustrating the present invention and are not intended to limit the protection scope of the present invention. In addition, it should also be understood that after reading the technical content of the present invention, those skilled in the art can make various changes, modifications and / or variations to the present invention, and all these equivalent forms also fall within the protection scope defined by the appended claims of this application.

Claims

1. A cutting protection liquid for InP wafers, which, by mass, comprises the following components: Side-chain phenyl resin: 10 - 40 parts Compound emulsifier: 0.5 - 5 parts Leveling agent: 0.5 - 5 parts Deionized water: 20 - 60 parts The side-chain phenyl resin is a styrene-styrenesulfonic acid copolymer with a number-average molecular weight of 1,000 - 50,000; The compound emulsifier is composed of an anionic emulsifier and a non-ionic emulsifier with a mass ratio of 1:1.5 - 5; The anionic emulsifier is sodium dodecylbenzenesulfonate; the non-ionic emulsifier is Tween-20.

2. The cutting protection liquid according to claim 1, characterized in that: The number-average molecular weight of the side-chain phenyl resin is 3,000 - 10,000.

3. The cutting protection liquid according to claim 1 or 2, characterized in that: The compound emulsifier is composed of sodium dodecylbenzenesulfonate and Tween-20 with a mass ratio of 1:

3.

4. A preparation method of the cutting protection liquid according to any one of claims 1 - 3, the preparation method comprising the following steps: A1: Weigh the required amount of deionized water; A2: Weigh the required amounts of anionic emulsifier and non-ionic emulsifier; A3: Mix the above components evenly and stir for 1 - 2 hours to obtain a mixed liquid; A4: Weigh the required amount of side-chain phenyl resin, add it to the mixed liquid under stirring, and continue stirring for 2 - 4 hours until a transparent emulsion is obtained; A5: Add the required amount of leveling agent to the transparent emulsion, and stir at room temperature for 0.5 - 1 hour until uniform, thus obtaining the cutting protection liquid.

5. Use of the cutting protection liquid according to any one of claims 1 - 3 in the cutting protection of InP wafers.

6. A cutting protection method for InP wafers using the cutting protection liquid according to any one of claims 1 - 3, the method comprising the following steps: B1: Drop 10 - 50 ml of the protection liquid onto the surface of the InP wafer, and rotate it at a speed of 500 - 1,500 r / min for 30 - 60 s using a spin coater; B2: Bake the wafer with the protection liquid spin-coated on its surface at 65 - 75 °C for 60 - 90 min to cure into a film and form a protection layer; B3: Cut the wafer with the protection layer on its surface, and enter the next process after cleaning.

7. A cleaning method for cleaning the protection layer formed by the protection liquid according to any one of claims 1 - 3 using a cleaning liquid, which, by mass, comprises the following components: Water-soluble surfactant: 5 - 20 parts Corrosion inhibitor: 1 - 5 parts Ultra-pure water: 50 - 80 parts The water-soluble surfactant is sodium dodecylbenzenesulfonate; The corrosion inhibitor is a mixture of L-cysteine and sodium alginate with a mass ratio of 1:1 - 3; The cleaning method comprises the following steps: S1: Place the wafer coated with the protection layer in cleaning tank 1 filled with the cleaning liquid, and soak it at a temperature of 50 - 60 °C for 15 - 20 min; S2: Transfer the wafer to cleaning tank 2 filled with the cleaning liquid, and soak it at a temperature of 50 - 60 °C for 15 - 20 min; S3: Transfer the wafer to the cleaning tank 3 filled with the cleaning liquid, and soak it at a temperature of 50 - 60 °C for 15 - 20 min; S4: Transfer the wafer to the spraying area, and thoroughly clean the cleaning liquid on the front and back of the wafer with ultrapure water; S5: Transfer the wafer to the air drying area, and dry the back of the wafer with hot nitrogen; S6: Transfer the wafer to the cleaning machine, rotate it at a speed of 1000 - 1500 r / min for 120 - 360 s, and spray ultrapure water onto the wafer surface at a flow rate of 400 - 600 mL / min during this period; S7: Stop spraying ultrapure water, rotate the wafer at a speed of 1500 - 2000 r / min for 120 - 360 s to spin-dry it, and complete the cleaning process of the protective layer.

8. The cleaning method according to claim 7, wherein: The preparation method of the cleaning liquid is as follows: Weigh each component respectively, then add the water-soluble surfactant and the corrosion inhibitor to ultrapure water, stir well, and then filter through a 0.2 μm microporous filter membrane to obtain the cleaning liquid.

Citation Information

Patent Citations

  • Protection liquid for metal substrate of semiconductor wafer and application method thereof

    CN102227688A

  • Method for wafer dicing and composition useful thereof

    CN102311863A